The Influence of Brand Image, Promotion and Product Quality on The Decision to Purchase A Honda Capella Batam Motorcycle - Syntia, Kartini; Realize, Realize (Jurnal Ilmiah Manajemen dan Bisnis, 2024)
Need will increasing transportation _ increase open opportunity for industry automotive  specifically sector motorcycle . Many _ vehicle wheel two on the market _ moment This with various models, designs and tempting promotions , as well the price is equivalent with other companies and capable give product quality . Research purposes This is For know influence between variable brand image , promotion , and quality product to decision purchase of a Honda Capella Batam motorbike. Determination technique big sample using non-probability sampling. Data is processed using SPSS version 25. Analysis Method can started after all data from respondents and other sources have collected . With results study show that brand image , promotion and quality product in a way Partial influential positive and significant to decision Purchasing a Honda Capella motorbike, Batam . Based on anova test results with calculated f value > table f and sig < 0.05. Can concluded that variable brand image , promotion and quality product to own influence positive and significant to decision purchase